2017
DOI: 10.1021/acs.iecr.6b04462
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-Phase Deposited Chlorosilane-Based Self-Assembled Monolayers on Various Substrates for Thermal Stability Analysis

Abstract: Chlorosilane-based self-assembled monolayers (SAMs), including octyltrichlorosilane (C8-OTS), (tridecafluoro-1,1,2,2-tetrahydrooctyl) trichlorosilane (FOTS) and dimethyldichlorosilane (DDMS), are applied on various substrates via a vapor-phase coating process for thermal stability analysis. Si(100) wafer dies and commercial vaporphase-deposited nanoparticle films are utilized as substrates to characterize the thermal stability enhancement. Atomic-force microscopy data prove that the vapor-based deposition tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The water contact angle is 103 • ± 2 • and 108 • ± 3 • for OTS and PTES, respectively. This is in good agreement with previous reported value for the water contact angle of OTS and PTES monolayer on SiO 2 [8,21].…”
Section: Preparation Of Octadecyltrichlorosilane(ots) and Ptes On Siosupporting
confidence: 93%
See 1 more Smart Citation
“…The water contact angle is 103 • ± 2 • and 108 • ± 3 • for OTS and PTES, respectively. This is in good agreement with previous reported value for the water contact angle of OTS and PTES monolayer on SiO 2 [8,21].…”
Section: Preparation Of Octadecyltrichlorosilane(ots) and Ptes On Siosupporting
confidence: 93%
“…In addition, the physical and chemical properties of SAMs can be manipulated by simply choosing the terminal group of precursor molecules with different functionalities. For example, the methyl group of octadecyltrichlorosilane (OTS) reduced the susceptibility to stiction [8], and the trifluoromethyl group of perfluorodecyltrichlorosilane (FDTS) resulted in highly hydrophobic and oleophobic monolayers, which prevented the device from adsorption of ambient moisture and other materials [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…SAMs are usually deposited on surfaces by solution-based methods. , However, solution-based techniques are more challenging to integrate with the industrial fabrication of semiconductor devices due to processing times that can approach 24 h. In addition to the solution-based method, SAMs can also be formed through the vapor phase. While several studies have shown that the quality of vapor-deposited SAMs is comparable to the ones formed in solution, , inhibitors with about 12–18 carbon atoms in the tail group, which are most effective in blocking ALD, are difficult to deliver through the gas phase. To overcome this, small-molecule inhibitors are being considered for deactivating the nongrowth surface.…”
Section: Introductionmentioning
confidence: 99%
“…A broken Teflon layer would destroy hydrophobicity and render the EWOD devices ineffective, causing them to quickly break down. Because the silane layer exhibits higher thermal stability [108], we added it on top of the Teflon to ensure hydrophobic stability of the EWOD device under long-term exposure to steam flow. The silane layer was obtained via vapor deposition.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…We placed the samples in a vacuum chamber and let the vacuum run for 2h. A monolayer of silane was deposited after vapor deposition [108]. The silane layer was not considered in the thermal resistance calculation due to its negligible thickness.…”
Section: Experimental Apparatusmentioning
confidence: 99%